2009
DOI: 10.1093/rheumatology/kep367
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of fatigue correlates in rheumatoid arthritis and osteoarthritis: disparity in associations with disability, anxiety and sleep disturbance

Abstract: Fatigue is common and severe in both RA and OA. In RA, fatigue had no significant association with pain, disease activity, disability or erosions, but was associated with depression and anxiety. The disparity in correlates indicates that generalizing the experience of fatigue between OA and RA is not appropriate. Fatigue is an important domain in the assessment of disease impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
72
2
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 34 publications
10
72
2
7
Order By: Relevance
“…As well, 21 percent of the knee osteoarthritis cases and 22.8% of hand osteoarthritis cases had scores greater than 19, rates of clinically depression that were higher than those recorded in a previous study by Abdel-Nasser et al of 10% for adults with knee osteoarthritis, but comparable to cases with rheumatoid arthritis, thought to be a more severe disease, where 23% of the sample were found to have clinically confirmed depression [68]. Similarly, in a study by Stebbings et al [69], participants with osteoarthritis reported greater pain, disability, depression and sleeplessness than those with rheumatoid arthritis (all p<0.01). In those with osteoarthritis, the correlates of fatigue, often not associated strongly with osteoarthritis, were older age (p=0.02), sleep disturbances (p=0.03), depression (p=0.04), disability (p=0.04) and lower C-Reactive Protein (p=0.001).…”
Section: Need For Interventions To Decrease Depressionmentioning
confidence: 80%
“…As well, 21 percent of the knee osteoarthritis cases and 22.8% of hand osteoarthritis cases had scores greater than 19, rates of clinically depression that were higher than those recorded in a previous study by Abdel-Nasser et al of 10% for adults with knee osteoarthritis, but comparable to cases with rheumatoid arthritis, thought to be a more severe disease, where 23% of the sample were found to have clinically confirmed depression [68]. Similarly, in a study by Stebbings et al [69], participants with osteoarthritis reported greater pain, disability, depression and sleeplessness than those with rheumatoid arthritis (all p<0.01). In those with osteoarthritis, the correlates of fatigue, often not associated strongly with osteoarthritis, were older age (p=0.02), sleep disturbances (p=0.03), depression (p=0.04), disability (p=0.04) and lower C-Reactive Protein (p=0.001).…”
Section: Need For Interventions To Decrease Depressionmentioning
confidence: 80%
“…First, we did not perform a radiographic evaluation of the joints. In RA patients, fatigue had no significant association with pain, disease activity, and disability or bone erosions but was associated with depression and anxiety (25). Therefore, it is unlikely that depression is directly linked to a radiographic evaluation.…”
Section: Discussionmentioning
confidence: 92%
“…This VAS had no calibration marks and end descriptors 'Full nights sleep' and 'No sleep at all' . A similar method has been used previously in studies examining the patients with Rheumatoid Arthritis and Osteoarthritis [18].…”
Section: Methodsmentioning
confidence: 99%